2019
DOI: 10.1111/pce.13646
|View full text |Cite
|
Sign up to set email alerts
|

Halotropism requires phospholipase Dζ1‐mediated modulation of cellular polarity of auxin transport carriers

Abstract: Endocytosis and relocalization of auxin carriers represent important mechanisms for adaptive plant growth and developmental responses. Both root gravitropism and halotropism have been shown to be dependent on relocalization of auxin transporters. Following their homology to mammalian phospholipase Ds (PLDs), plant PLDζ‐type enzymes are likely candidates to regulate auxin carrier endocytosis. We investigated root tropic responses for an Arabidopsis pldζ1‐KO mutant and its effect on the dynamics of two auxin tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Halotropism is an auxin-dependent root growth away from higher salt concentrations and toward areas with lower salt concentrations. Although previous studies identified auxin transporters to have contributory roles in root halotropic responses (Galvan-Ampudia et al., 2013, Korver et al, 2019, van den Berg et al., 2016), other components of this process remain largely unknown. Here, we screened a set of 333 Arabidopsis accessions using the robust and efficient halotropism assay and associated the observed root phenotypes with SNP markers using GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…Halotropism is an auxin-dependent root growth away from higher salt concentrations and toward areas with lower salt concentrations. Although previous studies identified auxin transporters to have contributory roles in root halotropic responses (Galvan-Ampudia et al., 2013, Korver et al, 2019, van den Berg et al., 2016), other components of this process remain largely unknown. Here, we screened a set of 333 Arabidopsis accessions using the robust and efficient halotropism assay and associated the observed root phenotypes with SNP markers using GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…A typical example of such an adaptive response is a rapid bending of roots away from high-salt-containing environments, which is known as halotropism ( Rosquete and Kleine-Vehn, 2013 ). The halotropic bending of roots is a result of tuning PAT that leads to asymmetric redistribution of auxin at the root tip ( Galvan-Ampudia et al., 2013 , van den Berg et al., 2016 , Korver et al., 2020 ). It has been shown that on the side of root that faces a high-salinity environment, clathrin-mediated endocytosis of PIN2 is increased.…”
Section: Hormonal Regulation Of Subcellular Trafficking Of Auxin Tranmentioning
confidence: 99%
“…Consequently, as result of the reduced amount of PIN2 at the PM in epidermal cells at the salt exposed side of the root, auxin at the root tip is asymmetrically redistributed, which steers the root away from the salty surroundings ( Galvan-Ampudia et al., 2013 ). Phospholipases (PLDs) and phosphatidic acid (PA), a signaling molecule formed by the action of PLD, have been identified as important molecular players in the regulation of auxin transport mediated through AUX1 and PIN2 in response to salt stress ( Li and Xue, 2007 , Testerink and Munnik, 2011 , Galvan-Ampudia et al., 2013 , Korver et al., 2020 ). Salt-induced stimulation of PLD activity increases the clathrin-mediated endocytosis of PIN2 at the side of the root facing the higher salt concentration, suggesting that PA controls the polar distribution of PIN and auxin polarity during halotropism in plants ( Galvan-Ampudia et al., 2013 ).…”
Section: Hormonal Regulation Of Subcellular Trafficking Of Auxin Tranmentioning
confidence: 99%
“…Phospholipid signaling is also critical in inducing halotropic movement of roots. Phospholipase Dζ1 can modulate the cellular polarity of auxin transport carriers ( Korver et al., 2020 ). Another issue to be answered is the contribution of tissue-specific accumulation of pH-sensing phosphatidic acid to the halotropism ( Li et al., 2019 ).…”
Section: Components Of Cellular and Physiological Features Of Root Hamentioning
confidence: 99%